Repetitive transcranial magnetic stimulation for stroke rehabilitation: insights into the molecular and cellular mechanisms of neuroinflammation - Sheng, Rongjun; Chen, Changchun; Chen, Huan; Yu, Peipei (Frontiers in Immunology, 2023)
Stroke is a leading cause of mortality and disability worldwide, with most survivors reporting dysfunctions of motor, sensation, deglutition, cognition, emotion, and speech, etc. Repetitive transcranial magnetic stimulation (rTMS), one of noninvasive brain stimulation (NIBS) techniques, is able to modulate neural excitability of brain regions and has been utilized in neurological and psychiatric diseases. Moreover, a large number of studies have shown that the rTMS presents positive effects on function recovery of stroke patients. In this review, we would like to summarized the clinical benefits of rTMS for stroke rehabilitation, including improvements of motor impairment, dysphagia, depression, cognitive function, and central post-stroke pain. In addition, this review will also discuss the molecular and cellular mechanisms underlying rTMS-mediated stroke rehabilitation, especially immune regulatory mechanisms, such as regulation of immune cells and inflammatory cytokines. Moreover, the neuroimaging technique as an important tool in rTMS-mediated stroke rehabilitation has been discussed, to better understanding the mechanisms underlying the effects of rTMS. Finally, the current challenges and future prospects of rTMS-mediated stroke rehabilitation are also elucidated with the intention to accelerate its widespread clinical application.